2018
DOI: 10.1161/jaha.118.010139
|View full text |Cite
|
Sign up to set email alerts
|

Gait Speed and 1‐Year Mortality Following Cardiac Surgery: A Landmark Analysis From the Society of Thoracic Surgeons Adult Cardiac Surgery Database

Abstract: Background In older adults undergoing cardiac surgery, prediction of downstream risk is critical. Our objective was to determine the association of 5‐m gait speed with 1‐year mortality and repeat hospitalization following cardiac surgery. Methods and Results In this prospective cohort of patients undergoing cardiac surgery at centers participating in the Society of Thoracic Surgeons Database with gait speed recorded, we examined all‐cause mortality using a landmark anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…29 There is a relation between low gait speed and increased mortality in elderly patients undergoing cardiac surgery. 30,31 In a study by Kamiya and colleagues gait speed was comparable to the 6MWT in a subgroup of patients undergoing cardiac surgery. 31 No studies have compared gait speed with 6MWT with regard to myocardial injury and mortality in patients undergoing non-cardiac surgery.…”
Section: The Literaturementioning
confidence: 95%
“…29 There is a relation between low gait speed and increased mortality in elderly patients undergoing cardiac surgery. 30,31 In a study by Kamiya and colleagues gait speed was comparable to the 6MWT in a subgroup of patients undergoing cardiac surgery. 31 No studies have compared gait speed with 6MWT with regard to myocardial injury and mortality in patients undergoing non-cardiac surgery.…”
Section: The Literaturementioning
confidence: 95%
“…The reliability was lower when using the first and second trials, the first and third or the three trials. Most of studies on gait used the average of three trials in various populations (e.g., healthy [ 50 , 79 ] or pathological [ 80 ]), but the number of trials necessary to obtain reliable measurements has been poorly investigated [ 28 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that gait speed had a prognostic value on 100-day mortality ( p = 0.005, HR 3.43) [ 38 ]. In the study of Afilalo et al, gait speed was studied for one-year mortality specifically following cardiac surgery [ 39 ].…”
Section: Discussionmentioning
confidence: 99%